ALAT UJI MICRO DEVAL SEBAGAI ALTERNATIF PENGUJIAN DURABILITI AGREGAT - Djoko Widajat (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Micro Deval has been developed in Europe as aggregate wear test, however from one of the specification used in this country not only Micro Deval was used to classify aggregate type but also Los Angeles Abrasion Value. Data show that LAA Value increases as Micro Deva l value increases, but some data show that the value of LAA is low while the micro deval value is high. Micro deval can be used to test the aggregate wear in wet condition.